Tetralogy of Fallot with Absent Pulmonary Valve Syndrome with Absent Left Pulmonary Artery - A Rare Presentation (Bangladesh Heart Journal, 2020)
Absent left pulmonary artery with Tetralogy of Fallot (TOF) with absent pulmonary valve syndrome (APVS), is a rare congenital cardiac anomaly. Here we present such a case of A 2 year 11 month old girl with cyanosis, exertional dyspnoea. Her diagnosis is confirmed by echocardiography and CT angiogram. There are very few cases have been reported till date with high postoperative mortality. Although per operative decision making was challenging regarding pulmonary valve and size of the RPA, we performed ICR with RPA reductionplasty and creation of monocuspid pulmonary valve with success. As it is a rare association and we have overcome the hindrance we came across per operatively, we are reporting this case.Bangladesh Heart Journal 2020; 35(1) : 74-77